Diet Induced Variation in Gut Microbiota Is Linked to the Growth Performance of an Agricultural Pest Chilo suppressalis - Peipei Zhu; Beshoy Mamdouh; Mahmoud Magdy; Jingnan Chen; Weihua Ma; Letian Xu (Agronomy, 2023)
Chilo suppressalis is a major global host-specific pest of rice and water oat crops, having caused severe yield damage and great economic loss. The pest occasionally feeds on other plants, preventing them from completing a full life cycle. Dietary differences may shape the gut microbiota of the pest and may further influence its performance. In order to test this hypothesis, an assembly of the gut bacterial community of C. suppressalis larvae reared on rice, water oat, corn, and an artificial diet were investigated using an amplicon-based next-generation sequencing approach. The larval body size and feeding rate on each diet type were analyzed in parallel. We found that the size and feeding rate of C. suppressalis varied among the different dietary regimes, as a low feeding rate was found for rice and corn diets, whereas rice-fed larvae had the biggest body size and corn-fed larvae had the lowest body size. Further high-throughput sequencing results showed that the artificial-diet-fed larvae had the lowest bacterial diversity among all the samples, and the corn-fed larvae presented the most diversified microbial community. Further analysis revealed that the bacterial genera Enterococcus, Sphingobacterium, Klebsiella, Gluconobacter, Serratia, and Lactococcus possessed high abundance in C. suppressalis larvae, and the varied abundances contributed to the differences in community structure. The microbial function classification suggested that metabolic function categories significantly increased while the larvae were feeding on their preferred diet (rice and water oat) and decreased when on an artificial diet. This study expands our understanding of the microbe–insect interaction of C. suppressalis larvae in response to changes in diet, and is an essential step towards the future development of potential microbial-based pest management strategies.